Effects of structure parameters on flow and cavitation characteristics within control valve of fuel injector for modern diesel engine. (15th September 2016) - Wang, Chao; Li, Guo-Xiu; Sun, Zuo-Yu; Wang, Lan; Sun, Shu-Ping; Gu, Jiao-Jiao; Wu, Xiao-Jun
Highlights: The Schnerr-Sauer model was used to calculate the cavitation source term. The development process and influencing factors of cavitation were studied. The flow process inside control valve during the ball valve opened were studied. The effects of the structure parameters of the control valve on the cavitation and flow were studied. Abstract: Cavitation is a common phenomenon in diesel injector and has a strong influence on the internal flow. However, studies so far have focused on cavitation characteristics inside the nozzle. Its influence on the flow during control valve opening remains still unclear. In the paper, a computational study focused on the flow and cavitation phenomena within control valve has been reported and the effects of control valve's structure parameters (including rounded edge, seal cone angle and outflowing control-orifice structure) on the flow and cavitation characteristics have been investigated in detail. Firstly the 3D model has been validated in terms of single injection quantity and fuel injection duration, showing a good consistency. And then, the development from sheet cavitation to cloud cavitation and the relationship between cavitation, pressure and velocity has been discussed. Based on the numerical results obtained, it is shown that not only the variation of pressure but also the velocity is the important factor which affects cavitation. The increase of the flow velocity reduces the pressure within the flow field which can aggravate the development of cavitation. As cavitation region increases, the fuel flow is hindered and the flow velocity decreases. However, the decrease of flow velocity has suppressed the development of cavitation. All of those variations form a cyclical process.